Comparative Analysis of Flavonoid Content and DPPH Antioxidant Activity of Black Soybean (Glycine soja) Extract and Its Solvent Fractions - Putri, Annisa Ayu Widya; Pramukantoro, Ganet Eko; Novita, Mega; Marlina, Dian (The Journal of Pure and Applied Chemistry Research, 2026)
Free radicals are known contributors to various degenerative diseases, highlighting the importance of antioxidants in mitigating their harmful effects. Black soybean seeds (Glycine soja) are acknowledged for their antioxidant properties attributed to flavonoid components.  The purpose of this work was to assess the antioxidant capacity and flavonoid content of the ethanol extract and its separated fractions, n-hexane, ethyl acetate, and aqueous, that were extracted from black soybean seeds.  The DPPH radical scavenging technique was used to assess antioxidant capacity, and a colorimetric method was employed to determine flavonoid concentration. The findings indicated that the maximum flavonoid content was found in the ethyl acetate fraction (1.72% ± 0.13), and that this fraction also exhibited the strongest antioxidant activity (IC₅₀: 27.43 ± 0.24 ppm), classified as very strong. The water fraction also exhibited very strong antioxidant activity (IC₅₀: 42.44 ppm ± 0.11), while the n-hexane fraction showed strong activity (IC₅₀: 61.25 ppm ± 0.73). Results indicate that the black soybean seed ethyl acetate extract has substantial antioxidant properties and may be useful in the creation of pharmaceutical or nutraceutical goods.